A relação discente no processo de busca em fontes de informação da Biblioteca do Sertão (BISER/UFS) relacionado ao uso da aprendizagem de metodologias ativas na UFS – Campus Sertão - Rodrigues, Dayse Lima (2021)
Traditional classes represent a form of teaching that is still very visible in the various existing Universities, allowing the teacher to be active in conducting the taught content, leaving students in a more passive position. The arrival of Active Methodologies represents a significant change in the way these students learn, making them more responsible for their own learning. The search for information linked to new teaching methodologies awakens in the students a need for research that is effective, causing in them different feelings in the face of confusion in not knowing which way to go until the arrival of these sources of information. The work aims to identify how the six dimensions of the ISP model of researcher Carol Kuhlthau are characterized in relation to the information-seeking behavior of 1st and 2nd cycle students at the Federal University of Sergipe-Campus do Sertão, which has its curriculum focused on this new teaching and learning method. Through descriptive and bibliographical research with application of questionnaires, it is possible to verify which sources are most used by them; if teachers participate in this search process, identify what feelings exist in the process and find out how well their information skills are developed in relation to the use of informational and technological resources present in the BISER- Biblioteca do Sertão. The results obtained show that students have greater difficulties associated with Active Methodology, since they have been accustomed to the traditional teaching method for many years, having their first contact with Active Methodology when entering graduation.